Strengthening English Language Learning Through an Independent Curriculum Approach - Ratna Rintaningrum; Arfan Fahmi; Kartika Nuswantara; Umi Trisyanti; Khanan Yusuf; Siti Zahrok (GoAcademica Research & Publishing, 2023)
This research aims to investigate the effectiveness of the